PEMANFAATAN BUNGA PUKUL DELAPAN (Turnera subulata) SEBAGAI TANAMAN INANG BAGI PREDATOR DAN PARASITOID ULAT API (Studi Kasus PT. Tritunggal Sentra Buana) - Ismail Ismail; Rusli Anwar; Wartomo (Politeknik Pertanian Negeri Samarinda, 2021)
This research is motivated by the importance of knowledge about alternative pest control that is safe but still supports the achievement of maximum oil palm production so that the balance of the oil palm plantation ecosystem can occur. The purpose of this study is to determine the technical cultivation and benefits of the Turnera subulata flower as a host plant for predators and parasitoids that function as biological agents for caterpillars and can be a reference for controlling caterpillar pests that are safe and still support the achievement of maximum oil palm production. The method used in this research is field observation and documentation from the company. The scope of this research covers the technical aspects of the biological control of caterpillars. This research data uses primary data and secondary data obtained from field observations and literature studies in the form of company reports in the form of percentages. The realization of Turnera subulata planting reached 21,659 m on CR road and 19,914 m on MR road. The planned planting of Turnera subulata is 57,200 m on the CR road and 45,823 m on the MR road. For the realization of the planting of Turnera subulata itself using seeds that are ready for planting. To obtain the seedling, the company conducts its nurseries. The seedling technique was done using the stem cutting technique. The stems for the cutting technique were taken from the Turnera subulata plant stems that have grown large. The type of stem taken is the old Turnera subulata plant stem. For seed care, the seeds are always watered every morning and evening like other flower plants. For the natural enemy insects, been proven that there are 6 natural enemy insects associated with Turnera subulata plants, 3 predators, and 3 parasitoids, each with a large enough number of insects. The types are Eocanthecona furcellata, Cosmolestes sp., Sycannus dichotomus, Spinaria spinator, Fornicia sp., and Chaetexorista javana. The development and the implementation of a control system are by optimizing the conservation and utilization of these biological control agents is a wise step to obtain an effective, efficient and environmentally friendly technique for controlling caterpillars. The presence of Turnera subulata plants can be used to suppress the development of pests in oil palm plantations by increasing the potential for natural enemies, both predators, and parasitoids. The diversity of wild plants with flowers can increase the variety of insects so that the balance of the ecosystem occurs.